Insights into the history and timing of post-European land use disturbance on sedimentation rates in catchments draining to the Great Barrier Reef. (June 2018) - Bartley, Rebecca; Thompson, Chris; Croke, Jacky; Pietsch, Tim; Baker, Brett; Hughes, Kate; Kinsey-Henderson, Anne
Abstract: Sediment runoff has been cited as a major contributor to the declining health of the Great Barrier Reef (GBR), however, climate and land use drivers have not been jointly evaluated. This study used alluvial archives from fluvial benches in two tributaries of the Upper Burdekin catchment together with the best available land use history and climate proxy records to provide insights into the timing of depositional events in this region over the past 500 years. This study suggests that mining and the increased runoff variability in the latter half of the nineteenth century are the likely sources of the original excess sediment that was used to build the bench features in these catchments. Grazing also contributed to increased bench sedimentation prior to 1900, however, the contribution of grazing was likely more significant in the second half of the 20th century, and continues to be a dominant land use contributor today. Graphical abstract: Highlights: Sedimentary analysis and OSL dating are used to evaluate bench formation. Alluvial bench formation in the Burdekin pre-dates major European land use change. Runoff variability, mining and grazing are all contributors to bench formation. Fine (silt and clay) sediment stored in benches is very low (~4%). Represents ~16% of the fine sediment available (in parent material) for erosion